Synthesis and characterization of new thienylpyrrolyl-benzothiazoles as efficient and thermally stable nonlinear optical chromophores - Batista, Rosa Maria Ferreira (2007)
The synthesis and full characterization of new chromophores with second-order nonlinearities containing thienylpyrrolyl and benzothiazolyl moieties are reported. The solvatochromic behavior of the compounds was investigated. The hyperpolarizabilities _ of derivatives 4-6 were measured using hyper-Rayleigh scattering and thermogravimetric analysis (TGA) was used to evaluate their thermal stability. The experimental results indicate that good nonlinearity–thermal stability is well balanced specially for chromophores 6b-c, making them good candidates for NLO applications.